NORMALISASI ALIRAN SUNGAI (DAS) DALAM MEWUJUDKAN PEMBANGUNAN KONDUSIF - Joko Sunaryo (Jurnal Marketing, 2019)
This article aims to find out the programs carried out by local governments in the context of Normalizing the watershed. This research uses descriptive method with a qualitative approach. Data collection techniques used were interviews with informants as many as 8 people. The results of the Normalization Study of the Watershed (DAS) of Central Rimbo Subdistrict, Bungo Regency have been carried out but have not been maximized due to the low level of public awareness and the lack of integration of spatial planning systems with rural areas.Constraints in Normalizing Watersheds Efforts made (1) Strengthening coordination and capacity (2) Placing apparatus human resources who truly understand watershed issues (3) Realizing participatory, responsive and democratic governance by prioritizing trust, a culture of hard work and high discipline and able to motivate the people.